2019
DOI: 10.1111/jch.13520
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and blood pressure in children: Analysis of the pan‐European IDEFICS cohort

Abstract: The present study aims to examine the cross-sectional and longitudinal association between self-reported nocturnal sleep duration, blood pressure, and hypertension in European children, aged 2-9.9 years, participating in the IDEFICS project. Blood pressure (BP) and the main anthropometric indices were measured according to standardized procedures. Childhood elevated BP and hypertension were defined according to the European Society of Hypertension Guidelines for children and adolescents. Parents reported lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Time spent using screen-based devices increases SB which has been linked with a higher intake of energy-dense snacks and drinks and fast foods, and an overall higher energy intake [15]. Short sleep duration has also been linked with the development of obesity [16] and high blood pressure in children [17] as well as with overall well-being [18]. In recent years and based on evidence of the importance of SB and sleep to health, several countries have shifted to providing integrated guidance for movement behaviours across the whole day (i.e., a 24-h period) including recommendations for PA, screen time, and sleep duration [19-21].…”
Section: Introductionmentioning
confidence: 99%
“…Time spent using screen-based devices increases SB which has been linked with a higher intake of energy-dense snacks and drinks and fast foods, and an overall higher energy intake [15]. Short sleep duration has also been linked with the development of obesity [16] and high blood pressure in children [17] as well as with overall well-being [18]. In recent years and based on evidence of the importance of SB and sleep to health, several countries have shifted to providing integrated guidance for movement behaviours across the whole day (i.e., a 24-h period) including recommendations for PA, screen time, and sleep duration [19-21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lower ST, higher cardiac output and incident aoBP component are determinants of BP levels. The referred factors could contribute to explain the negative association between ST and baBP reported in some works that did not include them in multiple regression analysis [50][51][52]. Regardingthis, in this work there was positive association between cardiac output and high baBP (Table 3).…”
Section: Sleep Time and Cardiovascular Inter-individual Variationsmentioning
confidence: 58%
“…In a review of these existing dangers, several types of interventions have been described to present conditions under which lifestyle conditions maybe altered to ensure neurodevelopmental and physiologic maturational health [29]. In a cross-sectional cum longitudinal association study between self-reported nocturnal sleep duration, blood pressure, and hypertension among European children, aged 2-9.9 years, a prospective analysis demonstrated that the presence of shorter sleep duration at baseline-level predicted, covering the 2-year follow-up period, greater increases in systolic blood pressure and diastolic blood pressure were observed, following the adjustment for age-level, gender, country of origin, body mass index z-score, parental education, physical exercise, screening time, and T0 critical value for the examined outcome variables [30].…”
Section: Literature Reviewmentioning
confidence: 99%